2006
DOI: 10.1509/jppm.25.2.238
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Assessment of Online Privacy Notice Readability

Abstract: This study evaluates the readability of a set of 312 online privacy notices across two periods and finds that the readability has declined and notices have grown in length over the period. The authors assess these findings against the public policy backdrop and make recommendations for improving current online privacy notices based on the study results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(65 citation statements)
references
References 23 publications
2
62
0
1
Order By: Relevance
“…Unlike gauges on an airplane or uniforms on the enemy, the IP context lacks the elements that individuals can use to increase their privacy awareness (companies' privacy policies are a potential exception, though its ability to notify the public has been debated) [28]. Since there is a lack of elements in IP, users must depend on their literacy (collection of knowledge dimensions) as a gauge to perceive the risk elements in IP.…”
Section: Endsley's Situation Awarenessmentioning
confidence: 99%
“…Unlike gauges on an airplane or uniforms on the enemy, the IP context lacks the elements that individuals can use to increase their privacy awareness (companies' privacy policies are a potential exception, though its ability to notify the public has been debated) [28]. Since there is a lack of elements in IP, users must depend on their literacy (collection of knowledge dimensions) as a gauge to perceive the risk elements in IP.…”
Section: Endsley's Situation Awarenessmentioning
confidence: 99%
“…"Choice" is a problematic concept when individuals perceive that opting out of application usage has more costs than benefits (Cate 2010). And surveys and experiments have shown that individuals make judgments about privacy expectations and violations regardless of the content of privacy notices (Milne, Culnan, and Greene 2006;McDonald and Cranor 2008;Beales and Muris 2008;Martin 2013;Nissenbaum 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Flesch reading ease and grade-level scores are two of the most commonly used measurements of readability for financial services advertising (e.g., Philpot and Johnson 2007) as well as other marketing studies (e.g., Milne et al 2006;Sheehan 2005) in terms of comparability and interpretability of advertising information to average consumers.…”
Section: Coding Procedures and Intercoder Reliabilitymentioning
confidence: 99%